Level Of Awareness of Pregnant Women Towards Dental and Oral Hygiene in Cemani Sukoharjo Village: Tingkat Kesadaran Ibu Hamil terhadap Kebersihan Gigi dan Mulut di Desa Cemani Sukoharjo - Kusuma, Mahera Perdana; Diwatri, Meita Rahma; Sari, Monita (Prosiding University Research Colloquium, 2024)
Background : Pregnancy is a natural condition that involves anatomical, physiological and hormonal changes. In hormonal changes there are effects that can affect all organ systems including the oral cavity. This condition occurs because there is an increase in levels of the hormones estrogen and progesterone during pregnancy which can cause an excessive increase in inflammatory response to plaque buildup in the oral cavity. Objective : To determine the level of awareness of oral health in pregnant women in Cemani Village, Sukoharjo. Method : The activity was carried out using the questionnaire method which was packaged using the pre test and post test methods as well as the demonstration method with posters. Conclusion : The level of awareness of pregnant women about dental and oral health in Cemani Sukoharjo Village is still relatively low. After the health promotion was carried out, the results showed that there was an increase in the knowledge and awareness of pregnant women regarding dental and oral hygiene.